Knowledge Management as innovation resource for Micro and Small Enterprises (MSE): the Enabling Knowledge Creation (EKC) model - Felipe, André Anderson; Mota, Denysson Axel Ribeiro (InCID: Revista de Ciência da Informação e Documentação, 2015)
This paper exposes and analyzes the model of Knowledge Management (KM), presented in the book Enabling Knowledge Creation from Von Krogh, Ichijo and Nonaka (2000), called here EKC model, tracing its main stages and forms of application. AS objective it analyzes how the guidelines for MSE innovation proposed by the Serviço Brasileiro de Apoio às Micro e Pequenas Empresas (SEBRAE) involve procedures from the GC, more specifically, how to configure front of the EKC model. The bibliographic and documental research was used as a methodological approach to present the EKC model, and the comparative analysis as a resource to provide an analysis of the guidelines of innovation for MSE proposed by SEBRAE and comparing them with the steps established by EKC model. The results show that guidelines for MSE innovation established by SEBRAE are close to the steps presented by the EKC model, demonstrating the relevance of KM in developing actions that promote ways to innovate in the Brazilian business context